Trans-Pacific relations : America, Europe, and Asia in the twentieth century - Jensen, Richard J.; Davidann, Jon Thares; 杉田, 米行 (Perspectives on the twentieth century, 2003)
This broad-based study of Western-Asian relations considers images of and actions by the United States, along with Britain and Germany, in the course of dealings with Asian nations such as China, Japan, Korea, Thailand, Vietnam, and the Philippines. Other case studies focus on inter-Asian relations between Japan and Korea; China and Japan; and Thailand and Vietnam. The essays encompass a wide range of recent scholarship, including cultural, economic, demographic, and intellectual approaches to military and diplomatic themes. Western influence, primarily American, in Asia grew consistently during the 20th century. While interaction often occurred on unequal terms, this study reveals the ability of Asians to assert their agency in the face of such immense Western power. The collection as a whole offers a window on relations across the Pacific in numerous spheres of activity over the course of one hundred years. As such, it introduces and adds to our understanding of the depth and variety of trans-Pacific relations.